Proceedings of the 2017 6th International Conference on Energy and Environmental Protection (ICEEP 2017) 2017
DOI: 10.2991/iceep-17.2017.72
|View full text |Cite
|
Sign up to set email alerts
|

Research and Application of Crystallization Technology in Treating Phosphorus Wastewater

Abstract: At present, the crystallization method has become a hotspot in the field of wastewater treatment. The crystallization method not only remove phosphorus effectively in wastewater, but the phosphorus also can be recycled. The crystallization method includes ammonium magnesium phosphate crystallization method, calcium hydroxy calcium phosphate crystallization method, vivianite crystallization method and so on. The study introduced the principle of phosphorus removal and the influencing factors of the three crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Many natural and synthetic adsorbents can be used for phosphate ions removal from wastewater such as coal fly ash, polymer hydrogels and industrial solid wastes like Fume Dust from Electric Arc Furnace (FD-EAF) 13 . In the crystallization process calcium reacts with hydroxide ions that exist in the aqueous alkaline solution to remove phosphate ions in the form of hydroxyapatite 10 , 14 . Due to the hydrophilic and three-dimensional polymeric network of polymer hydrogel, it is observed that polymer hydrogel is effective to be used as an adsorbent for phosphate ion removal from wastewater 9 , 14 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many natural and synthetic adsorbents can be used for phosphate ions removal from wastewater such as coal fly ash, polymer hydrogels and industrial solid wastes like Fume Dust from Electric Arc Furnace (FD-EAF) 13 . In the crystallization process calcium reacts with hydroxide ions that exist in the aqueous alkaline solution to remove phosphate ions in the form of hydroxyapatite 10 , 14 . Due to the hydrophilic and three-dimensional polymeric network of polymer hydrogel, it is observed that polymer hydrogel is effective to be used as an adsorbent for phosphate ion removal from wastewater 9 , 14 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In the crystallization process calcium reacts with hydroxide ions that exist in the aqueous alkaline solution to remove phosphate ions in the form of hydroxyapatite 10 , 14 . Due to the hydrophilic and three-dimensional polymeric network of polymer hydrogel, it is observed that polymer hydrogel is effective to be used as an adsorbent for phosphate ion removal from wastewater 9 , 14 16 . Because, nanomaterials/nanoparticles, snail shell dust and, carbon-based materials (activated carbon and biochar) have exceptionally high surface areas and phosphate adsorption properties, they are widely used for phosphate removal from wastewater 11 , 17 23 .…”
Section: Introductionmentioning
confidence: 99%